Investigation of human haemotropic Mycoplasma infections using a novel generic haemoplasma qPCR assay on blood samples and blood smears - Tasker, Séverine (Society for General Microbiology, 2010)
The aim of this study was to develop quantitative real-time (q)PCR assays to detect all known haemoplasma species, and a human housekeeping gene in order to demonstrate both successful DNA extraction from clinical samples and to test for sample inhibition, and to apply these qPCRs to human blood samples and blood smears. Sensitive and specific generic haemoplasma qPCR assays were developed to amplify haemoplasma species, as well as human glyceraldehyde-3-phosphate dehydrogenase (GAPDH) as an internal amplification control. An optimized technique for extracting DNA from stained blood smears was also developed. These methods were applied to anonymized blood samples obtained from 100 human immunodeficiency virus (HIV)-infected South Africans and 920 UK patients undergoing haematological examination, and to 15 blood smears recruited from previous studies describing human haemoplasmosis. Human GAPDH levels were acceptable in all but three of the blood samples and all but two of the blood smears. The latter could have arisen due to DNA degradation due to the old age (over 35 years) of these smears. Haemoplasma infection was found in one HIV-infected South African, but the species could not be characterized due to the very low levels of DNA present. This report describes novel extraction and qPCR methodologies for haemoplasma screening. Previously reported human haemoplasmosis based on cytological diagnosis alone should be viewed with caution.